Formation and inhibition of N-nitrosodiethanolamine in cosmetics under pH, temperature, and fluorescent, ultraviolet, and visual light. Issue 9 (3rd May 2018) - Lim, Duck Soo; Lim, Seung Kwang; Kim, Min Kook; Kwon, Yong Chan; Roh, Tae Hyun; Choi, Seul Min; Yoon, Sungpil; Kim, Hyung Sik; Lee, Byung-Mu
ABSTRACT: N-nitrosodiethanolamine (NDELA), a type of nitrosamine, is a possible human carcinogen that may form in cosmetic products. The aim of this study was to examine the formation and inhibition of NDELA through chemical reactions of secondary amines including mono-ethanolamine, di-ethanolamine (DEA), and tri-ethanolamine (TEA), and sodium nitrite (SN) under varying conditions such as pH, temperature, and fluorescent, ultraviolet (UV), and visual light (VIS) using liquid chromatography-mass spectroscopy. In a mixture of TEA and SN under acidic conditions pH 2, residual NDELA concentrations rose significantly under various storage conditions in the following order: 50°C > 40°C > UV (2 W/m 2 ) > VIS (4000 lux) > fluorescent light > 25°C > 10°C. In a mixture of DEA and SN under the same acidic pH 2 conditions, NDELA formation was significantly elevated in the following order: UV (2 W/m 2 ) > VIS (4000 lux) > 50°C > 40°C > fluorescent light > 25°C > 10°C. Inhibition of NDELA formation by d-mannitol, vitamin C (Vit C), or vitamin E (Vit E) was determined under varying conditions of pH, temperature, and fluorescent, UV, and VIS. At high concentrations of 100 or 1000 µg/ml, Vit E significantly decreased residual NDELA compared with control levels under acidic pH 2, but not under basic pH 6. Among various antioxidants, Vit E reacted more effectively with many nitrosating agents such as nitrate and nitrite found in cosmetic products. Therefore, to reduce NDELA, it is recommended that cosmetics be stored under cool/amber conditions and that Vit E or Vit C inhibitors of nitrosation be optimally added to cosmetic formulations at concentrations between 100 and 1000 µg/ml.